Fire forecasts July-September 2023: Western Amazon - Castaño, Silvia-Elena; Fernandes, Kátia; Calle, Carmen (2023)
July-September 2023 climate forecast points to an above normal fire season in western Amazon. Fires in the Amazon are the result of human activities, including the use of fire for deforestation, land clearing and agricultural maintenance. Most fires begin in non-forest areas that have already been cleared for agricultural use, but these fires can escape into neighboring forests and burn through the understory. Even these low-intensity surface fires kill most trees, since Amazon forests are not adapted to fire. Main results disseminated through the ArcGIS Storymap App: https://storymaps.arcgis.com/stories/38bea12b164e48acabae63187df00f3e (English)